Implementation of Fuzzy Logic in Determining Recommendations for Purchasing Folic Acid Supplements based on Fruit and Vegetable Consumption Patterns in Pregnant Mothers - Annisa Nurul Adelia; Al Zahra Dwi Pranata Lia Tanjung; Jesika Azura; Windy Anjeli Br Sitanggang; Sophia Solihati Devi; Syifa Hawasiatul Fikriyah; Myita Syabrina; Shafira Az-zahra; Ardya Hadi Kusuma; Muhammad Arsyad Budiman; Muhammad Danang Mukti Darmawan; Nanda Octavia; Ester Angeline; Fiqri Nurfadillah; Mrr. Lukie Trianawati (Batrisya Education, 2024)
This research aims to implement fuzzy logic in determining the level of recommendation for folic acid supplements based on the input of the amount of vegetable and fruit consumption and folic acid content. The output of the developed system is in the form of recommendation level with categories of